Development of eXeLearning-assisted E-Modules to Improve Students' Understanding of Uniformly Accelerated Motion Concepts - Erma Novela; Eko Risdianto; Rosane Medriati (Postgraduate, University of Mataram, 2023)
This study aims to describe the feasibility of eXeLearning-assisted e-modules on Uniformly Accelerated Motion material and describe increasing students' understanding of concepts after using eXeLearning-assisted e-modules on Uniformly Accelerated Motion material. The method used in this study is the Research and Development method with the ADDIE model. The subjects of this study were 32 students of class XI H SMAN 3 Kota Bengkulu. The data collection techniques are observation, interviews, expert validation, and tests. From the results of research conducted on the feasibility test, the results were obtained the average percentage of 5 aspects is 98.40% with a very decent category. Test results to determine the increase in students' understanding of the concept of eXeLearning-assisted e-modules on Uniformly Accelerated Motion material using N-gain calculations obtained an average pretest score of 52.31 and a posttest average of 91.40 and N-gain 0.81 of the high category. Thus, it can be concluded that after learning carried out using eXeLearning-assisted e-modules, there is a high increase in students' understanding of concepts in Uniformly Accelerated Motion material class XI SMAN 3 Kota Bengkulu